2017
DOI: 10.1186/s12955-017-0622-z
|View full text |Cite
|
Sign up to set email alerts
|

Glatiramer acetate treatment persistence - but not adherence - in multiple sclerosis patients is predicted by health-related quality of life and self-efficacy: a prospective web-based patient-centred study (CAIR study)

Abstract: BackgroundIn patients with relapsing remitting multiple sclerosis (RRMS) the persistence of and adherence to disease modifying drug (DMD) treatment is inadequate. To take individualised measures there is a need to identify patients with a high risk of non-persistence or non-adherence. As patient-related factors have a major influence on persistence and adherence, we investigated whether health-related quality of life (HRQoL) and self-efficacy could predict persistence or adherence.MethodsIn a prospective web-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…The unique contribution of HRQoL assessment to the evaluation of individual patients is illustrated by the fact that a permanent numbness at a fingertip will hardly have a functional effect in a construction worker, but may severely affect the occupational activities of a professional violinist. Recently, it has been reported that the levels of HRQoL and self-efficacy may predict the risk of early treatment discontinuation in patients starting high-frequency GA treatment [ 96 ]. When interpreting HRQoL changes over longer periods, response shift may be a concern as subjective self-reported outcomes may be influenced by adaptation to the illness [ 97 ], even in patients who are not actively experiencing symptoms on a consistent basis [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…The unique contribution of HRQoL assessment to the evaluation of individual patients is illustrated by the fact that a permanent numbness at a fingertip will hardly have a functional effect in a construction worker, but may severely affect the occupational activities of a professional violinist. Recently, it has been reported that the levels of HRQoL and self-efficacy may predict the risk of early treatment discontinuation in patients starting high-frequency GA treatment [ 96 ]. When interpreting HRQoL changes over longer periods, response shift may be a concern as subjective self-reported outcomes may be influenced by adaptation to the illness [ 97 ], even in patients who are not actively experiencing symptoms on a consistent basis [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to date numerous predictors of nonadherence have been identified in MS adherence studies, but no easy-to-use screening tool for predicting suboptimal implementation has been developed, whereas recently a proposition has been presented for identifying patients at risk of nonpersistence. 56 Future studies should also consider whether patients’ adherence prior to a DMT switch is predictive of outcome after switching to a further DMT. In this, it will be important to consider the application form (iDMTs, oDMTs, or ivDMTs), that it is not unusual for patients to take a drug holiday around the time of a switch, and that patient recall of prior adherence could be subject to recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…Nor are we aware of any studies focusing on the utility of illness representations within the theoretical framework of the CSM in the context of the adherence literature in MS, which could be seen as a construct related to service utilization. However, on a superordinate construct level, evidence suggests that adherence to disease-modifying therapies (DMT) is influenced by patients' attitudes and (adherence) expectations, treatment beliefs such as the perceived benefits of DMT therapy, and self-efficacy (Brandes, Callender, Lathi, & O'Leary, 2009;Jongen, Lemmens, Hoogervorst, & Donders, 2017;Turner, Kivlahan, Sloan, & Haselkorn, 2007;Turner, Roubinov, Atkins, & Haselkorn, 2016;Zwibel, Pardo, Smith, Denney, & Oleen-Burkey, 2011).…”
Section: Binary Logistic Regression (N = 473)mentioning
confidence: 99%